An Improved Maximum Power Point Approach for Temperature Variation in PV System Applications - Abdelkhalek Chellakhi; Said El Beid; Younes Abouelmahjoub (International Journal of Photoenergy)
This paper develops and discusses an improved MPPT approach for temperature variation with fast-tracking speed and reduced steady-state oscillation. This MPPT approach can be added to numerous existing MPPT algorithms in order to enhance their tracking accuracy and response time and to reduce the power loss. The improved MPPT method is fast and accurate to follow the maximum power point under critical temperature conditions without increasing the implementation complexity. The simulation results under different scenarios of temperature and insolation were presented to validate the advantages of the proposed method in terms of tracking efficiency and reduction of power loss at dynamic and steady-state conditions. The simulation results obtained when the proposed MPPT technique was added to different MPPT techniques, namely, perturb and observe (P&O), incremental conductance (INC), and modified MPP-Locus method, show significant enhancements of the MPP tracking performances, where the average efficiency of the conventional P&O, INC, and modified MPP-Locus MPPT methods under all scenarios is presented, respectively, as 98.85%, 98.80%, and 98.81%, whereas the average efficiency of the improved P&O, INC, and modified MPP-Locus MPPT methods is 99.18%, 99.06%, and 99.12%, respectively. Furthermore, the convergence time enhancement of the improved approaches over the conventional P&O, INC, and modified MPP-Locus methods is 2.06, 5.25, and 2.57 milliseconds, respectively; besides, the steady-state power oscillations of the conventional P&O, INC, and modified MPP-Locus MPPT methods are 2, 1, and 0.6 watts, but it is neglected in the case of using the improved approaches. In this study, the MATLAB/Simulink software package was selected for the implementation of the whole PV system.